Comparison of the effect of a period of TRX and yoga versus traditional exercises on balance of archers - Vazri, R. K. Z.; Entezari Khorasani, Z.; Balali, M.; Parvinpoor, S. (Health Nexus, 2024)
Archers engage in various exercises to maintain postural stability and balance to achieve peak performance in archery, as balance and fine motor control are critical components of success in this sport. Therefore, the aim of this study was to compare the effect of a period of TRX and yoga versus traditional exercises on the balance of archers. This study is quasi-experimental with a pre-test and post-test design. The present research is applied in nature and was conducted in the field. The statistical population included all male archers in Tehran Province aged 20 to 40 years. From this population, 30 individuals were selected based on inclusion and exclusion criteria through convenience sampling and then randomly assigned to three groups: traditional exercises, yoga, and TRX. In the pre-test, the balance in shooting was measured. After completing the measurements, each group received their respective exercises, and at the end of the last training session, the post-test including the measured variables was repeated. To examine the research hypotheses, initially, the normality of the data was checked using the Shapiro-Wilk test, which revealed that the data were not normally distributed. Therefore, non-parametric statistical tests were used for data analysis. The results of the Wilcoxon test indicated that all three types of traditional exercises, yoga, and TRX led to a significant improvement in balance, hand-arm stability, and performance of the archers. In the intergroup comparison using the Kruskal-Wallis test, it was found that there were significant differences among the three groups in the research variables. Pairwise comparisons using the Mann-Whitney U test revealed that TRX, yoga, and traditional exercises, respectively, had the most significant effects. Based on the obtained results, it is suggested that the training programs used in the present research, with priority given to TRX, yoga, and traditional exercises, be recommended for improving the balance of male archers.